Brain computer interface to answer yes-no questions - Roman Gonzalez, Avid (2017)
The aim of this work is to design, implement and validate a primary communication system based on a brain-computer interface. There are people who-for various reasons-are affected in their ability to externalize their communication, however, they receive and process information from different sources. This system would allow basic communication-allowing the user to answer closed questions-through thought. The system was implemented by analyzing and interpreting electrical signals from brain activity, collected through electrodes attached to the scalp. The analog electrical signals were received by a data acquisition system and digitized for computer analysis. We implemented different signal processing techniques, pattern analysis, and classification and discrimination methods. By analyzing these signals and interpreting the electrical patterns, was achieved understand answers to simple questions. The system has been validated testing with healthy volunteers in the laboratory, obtaining good results.